MANAJEMEN EKSTRAKURIKULER DALAM MEMBINA KARAKTER NASIONALIS PESERTA DIDIK SMAT KRIDA NUSANTARA BANDUNG - Muhammad Hasan Basari (Jurnal Ilmu Pendidikan dan Sosial, 2022)
The character of students is still a problem that continues to be discussed.Education prepares quality human resources, character, intelligent in thinking, skilled in work and polite in behavior and well educated, honest and has a high national spirit. This can be realized, among others, through extracurricular activities. Extracurricular activities are curricular activities carried out by students outside of learning hours for intracurricular activities and co-curricular activities, under the guidance and supervision of the education unit (Permendikbud, 2014). The purpose of this study is to describe the application of management in extra-curricular activities in fostering nationalist character of participants students. The research method used is a descriptive method with a qualitative approach and data collection techniques through observation, interviews and document studies. The findings show that the application of extracurricular management in fostering the nationalist character of students uses management according to management functions starting from planning, organizing, implementing and supervising.The conclusion is that extracurricular management in fostering the nationalist character in SMAT Krida Nusantara Bandung has made planning, organizing, implementing and controlling but not all of it is optimal.